2014
DOI: 10.1002/2013wr014829
|View full text |Cite
|
Sign up to set email alerts
|

Decadal surface water quality trends under variable climate, land use, and hydrogeochemical setting in Iowa, USA

Abstract: Understanding how nitrogen fluxes respond to changes in agriculture and climate is important for improving water quality. In the midwestern United States, expansion of corn cropping for ethanol production led to increasing N application rates in the 2000s during a period of extreme variability of annual precipitation. To examine the effects of these changes, surface water quality was analyzed in 10 major Iowa Rivers. Several decades of concentration and flow data were analyzed with a statistical method that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 47 publications
0
38
0
2
Order By: Relevance
“…Estimation by the WRTDS model was performed using measured chloride and corresponding daily streamflow values. This tool has not previously been used to examine chloride trends, but applications using WRTDS have primarily been used for examination of nutrients Medalie et al, 2012;Green et al, 2014).…”
Section: Modeling Water Quality Changesmentioning
confidence: 99%
“…Estimation by the WRTDS model was performed using measured chloride and corresponding daily streamflow values. This tool has not previously been used to examine chloride trends, but applications using WRTDS have primarily been used for examination of nutrients Medalie et al, 2012;Green et al, 2014).…”
Section: Modeling Water Quality Changesmentioning
confidence: 99%
“…In basins where agricultural activities dominate, it is common for the quality of water to be compromised (Green et al, 2014;Patoine et al, 2012;Volk et al, 2009). For example, in Denmark, Nielsen et al (2012) found a high correlation between the amount of agricultural land and the total nitrogen (N) and total phosphorus (TP) concentrations in adjacent lakes.…”
Section: Introductionmentioning
confidence: 99%
“…However, cleanup efforts at the larger scale may only show results after a few decades. A study examining NO 3 − and NO 2 − changes in Iowa (U.S.) from 1970 to 2012 suggested long-term N transport in watersheds due to fertilizer inputs on maize (Green et al, 2014). Since agricultural land can have such a variety of effects on water quality, investigating potential land use and management changes in a basin is necessary to achieve the WFD objectives which will be evaluated during planning cycles ending in 2015, 2021 and 2027.…”
Section: Introductionmentioning
confidence: 99%
“…However, the timing of nitrate-nitrogen concentration in surface water varies substantially across space and crop years due to weather (Jayasinghe et al, 2012) and other biophysical factors (Green et al, 2014). Thus, it would be difficult to obtain meaningful estimates of the effect of crop prices on observed nitrate-nitrogen concentrations, especially if one were to model the dynamics and spatial heterogeneity.…”
Section: Introductionmentioning
confidence: 99%